Research of snow melting materials performance efficiency for road winter maintenance - Laurinavičius, Alfredas; Čygas, Donatas; Vaitkus, Audrius; Ratkevičius, Tomas; Bulevičius, Matas; Mučinis, Darjušas; Baltrušaitis, Andrius (Transport, 2016)
In 2012, the Lithuanian Road Administration initiated a three-year research project ‘The study of effective winter road maintenance of national significance roads in Lithuania’. The main purpose of this research was to optimize road maintenance in winter and to determine the most effective means of combating slippery conditions. The research project was carried out by two institutions: the Road Research Institute of the Faculty of Environmental Engineering of Vilnius Gediminas Technical University and JSC ‘Problematika’. JSC ‘Problematika’ conducted exploratory experiments, which were divided into two phases. In the first phase of the experiment, five different snow melting materials (Slipperiness Reducing Materials – SRMs) were investigated in the laboratory. Different test methods were used in this investigation. In the second phase of the experiment, three SRMs with different properties were selected, and experimental road sections were set up to determine the road slipperiness and the change in coating layer thickness over time concerning different environmental conditions, as well as different snow and ice layer thicknesses. An optical remote sensor of Road Condition Monitor (RCM 411) was used for friction measurements on the roads. This report covers the laboratory test results of five different SRMs, road slipperiness measurement results using three selected SRMs and their analysis, comparison of the performance efficiency of the most widely used SRMs in Lithuania and the tested SRMs under different environmental conditions.